Locally rendered high-resolution Land Use/Land Cover Bitmaps from OpenStreetMap Data for geospecific 3D Simulation - D. Frommholz (ISPRS Annals of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
This paper describes a method for creating land use/land cover (LULC) bitmaps from OpenStreetMap data for virtually any part of the world at any resolution on a standard personal computer. The automatic workflow utilizes free software and open formats, does not require web services nor graphical GIS applications and can be run by novice cartographers. In the process, offline vector data sets from the collaborative mapping project are prepared into self-contained transferable database files that arrange relevant geometric features and attributes as spatially indexed tables for fast access. The database gets rendered into a georeferenced bitmap within minutes by the same engine as for the original OpenStreetMap tiles. In contrast to digital maps, the appearance of the output is altered with XML-based style sheets implementing filter rules to picture land cover classes according to various nomenclatures such as CORINE and Virtual Battlespace 4 (VBS4). For linear features like roads and railway tracks lacking a second dimension, the width is scaled to match real-world proportions. The scale factor passed to the style sheets is determined from the extent of the region to be rendered, the requested ground sampling distance, database hints and the latitude of the conformal target projection. Results for scenes around the world are visually analyzed, and a comparison to validated LULC data is conducted. As a showcase targeting security agencies, highly detailed land cover is integrated into a scene for the VBS4 3D simulator to model geospecific landscapes in real time.